2023
DOI: 10.3389/fphar.2023.1146966
|View full text |Cite
|
Sign up to set email alerts
|

N-methylsansalvamide elicits antitumor effects in colon cancer cells in vitro and in vivo by regulating proliferation, apoptosis, and metastatic capacity

Abstract: N-methylsansalvamide (MSSV), a cyclic pentadepsipeptide, was obtained from a strain of Fusarium solani f. radicicola. The current study investigated the anti-colorectal cancer effect of MSSV. MSSV exhibited the inhibition of the proliferation in HCT116 cells via induction of G0/G1 cell cycle arrest by downregulating CDK 2, CDK6, cyclin D, and cyclin E, and upregulating p21WAF1 and p27KIP1. Decreased phosphorylation of AKT was observed in MSSV-treated cells. Moreover, MSSV treatment induced caspase-mediated apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…CNL-619, consists of four hydrophobic amino acids [ L -Phe, L -Leu, N-methylleucine, and L -Val] and one hydroxy acid (O-Leu) (Figure 1) [7]. Park et al found that SA has an excellent inhibitory effect on colon tumors; its IC 50 concentration was observed at 24.05 ± 1.07 µM [8], suggesting it has therapeutic potential in treating cancers.…”
Section: Introductionmentioning
confidence: 99%
“…CNL-619, consists of four hydrophobic amino acids [ L -Phe, L -Leu, N-methylleucine, and L -Val] and one hydroxy acid (O-Leu) (Figure 1) [7]. Park et al found that SA has an excellent inhibitory effect on colon tumors; its IC 50 concentration was observed at 24.05 ± 1.07 µM [8], suggesting it has therapeutic potential in treating cancers.…”
Section: Introductionmentioning
confidence: 99%